Pembuatan Air Bersih Metode Destilasi Kjedahl dengan Kualifikasi Standar Baku Mutu - Artati, Yuniar; Fathirizki A.K, Kiamah; Rudangta Nasution, Denicha; Wirayuda, Ilham (JURNAL AGRIMENT, 2023)
Waste pollution pollutes land and water, causing the content of several chemicals to be at the threshold of safety standards and will have a negative impact on living things. One of the compounds often found in pollution cases is Nitrogen in the form of Organic Nitrogen and Inorganic Nitrogen which play a role in the Nitrogen (N) cycle. Research was carried out to determine the content of these three compounds using the Kjedahl distillation method using refill drinking water samples taken from the DAMIU. Kjedahl distillation will produce a Kjedahl Total Nitrogen (TNK) value which must be explained through further treatment, namely measurement using a Uv-Vis Spectrophotometer. The results showed NO2 values ​​of 0.603 mg/l (pre-distillation) and 0.443 mg/l (post-distillation) with a maximum limit of 20 mg/l, NO3 values ​​< 0.0005 mg/l (pre-distillation) and 0.026 mg/l (post-distillation) with a maximum limit of 3 mg/l and NH3 values ​​of 0.045 mg/l (pre-distillation) and 0.096 mg/l (post-distillation) with a maximum limit of 1.5 mg/l. Other supporting parameters tested to determine drinking water quality include physical parameters, chemical parameters and microbiological parameters. The conclusion that can be drawn is that the production of drinking distilled water using the Kjedahl method will produce distilled water that is free of minerals and of good quality. Apart from that, distilled drinking water also has many health benefits, including reducing the risk of disease and reducing the risk of exposure to dangerous chemicals because this water is pure, free of minerals and metals.. Keywords: water, distillation, nitrogen, kjedahl